Seismic Response of Anchor + Hinged Block Ecological Slope by Shaking Table Tests - Hui Su; Yijun Hang; Yongsheng Song; Kunming Mao; Dongyue Wu; Xiao Qiu (Advances in Materials Science and Engineering)
Landslides caused by earthquakes and other natural disasters may cause serious economic and personal losses. Slope protections are usually applied in engineering practice to prevent significant slope slides and damages. Based on the mechanical and ecological requirements on slope protections, this paper put forward a new type of anchor + hinged block ecological slope and carried out shaking table tests on it and other three traditional slope protections for comparing. By shaking table tests, the acceleration amplification factors and Fourier amplitude spectrums of four different slope types are analyzed and compared to verify the suitability of this new slope protection under earthquakes. The results indicated that the natural frequency and the acceleration Fourier amplitude spectrum of the four tested slope protections change according to internal materials. The anchor + hinged block ecological slope has higher natural frequency comparing to traditional slopes, so the resonance cycle from earthquake excitation can effectively be avoided and as a result the anchor + hinged block ecological slope can achieve better seismic performance.